Memadukan Style Flat Desain yang Modern dengan Konsep Islami di Festival Generasi Pemenang - Hakim, Moch. Rofi; Romadhona, Mahimma (Jurnal Ilmiah Wahana Pendidikan, 2024)
This journal explores efforts to combine modern flat design styles with Islamic concepts in the visual implementation of the Selamat Generation Festival. The flat design style, known for its minimalist tendencies and simplicity of visual elements, is integrated with Islamic values ​​to create an experience that blends contemporary aesthetics and religious spirituality. This research involved an in-depth analysis of the design process and implementation of the festival's visual elements including typography, color and layout. A participatory approach was used to evaluate participants' responses to the combination of modern flat design and Islamic concepts. Through interviews and observations, this research aims to explore how the combination of these elements can create a harmonious atmosphere and have a positive impact on participants' understanding of Islamic values ​​at the Generasi Winners Festival. The research results show that combining modern flat design with Islamic concepts is able to create a visual experience that enriches the meaning of religious festivals. These findings provide insight for festival organizers, designers and researchers to understand the potential for integrating modern aesthetics with religious values ​​within the scope of festivals. The practical implications of this research can be a guide for the development of more in-depth and contextual visual designs in the context of festivals that have high spiritual aspects such as the Generasi Juara Festival.